ALK‐Rearranged Non‐Small Cell Lung Cancer in 2020: Real‐World Triumphs in an Era of Multigeneration ALK‐Inhibitor Sequencing Informed by Drug Resistance Profiling. (2nd July 2020) - Itchins, Malinda; Lau, Brandon; Hudson, Amanda L.; Westman, Helen; Xia, Cathy Yi; Hayes, Sarah A.; Howell, Viive M.; Rodriguez, Michael; Cooper, Wendy A.; Wei, Heng; Buckland, Michael; Li, Bob T.; et al.
Abstract: : Since its discovery in 2007, we have seen the lives of patients diagnosed with advanced anaplastic lymphoma kinase ( ALK )‐rearranged non‐small cell lung cancers (NSCLC) transform with the advent of molecular therapies with first‐, second‐, and third‐generation ALK inhibitors now available in the clinic. Despite great gains in patient survival now measured in years and preserved quality of life with targeted therapies, drug resistance is unfortunately inevitably encountered in this rare and unique molecular subset of lung cancer, and patients will eventually succumb to the disease. As these patients are often young, fit, and never smokers, the clinical and scientific communities have aligned to expedite drug development and access. Drug resistance profiling and further strategies are being explored through clinical trials, including the evaluation of specific drug sequencing and combinations to overcome such resistance and promote patient longevity. The cases of this report focus on precision medicine and aim to portray the pertinent aspects to consider when treating ALK ‐rearranged NSCLC in 2020, an ever‐shifting space. By way of case examples, this report offers valuable information to the treating clinician, including the evolution of systemic treatments and the management of oligo‐progression and multisite drug resistance. With the maturation of real‐world data, we are fortunate to be experiencing quality and length of life for patients with this disease surpassing prior expectations in advanced lung cancer. Key Points: This report focuses on the importance of genetic analysis of serial biopsies to capture the dynamic therapeutic vulnerabilities of a patient's tumor, providing a perspective on the complexity of ALK tyrosine kinase inhibitor (ALKi) treatment sequencing. These case examples contribute to the literature on ALK ‐rearranged and oncogene addicted non‐small cell lung cancer (NSCLC), providing a framework for care in the clinic. In oligo‐progressive disease, local ablative therapy and continuation of ALKi postprogression should be considered with potential for sustained disease control. ALK G1202R kinase domain mutations (KDM), highly prevalent at resistance to second‐generation ALKi resistances, may emerge in non‐EML4‐ ALK variant 3 cases and is sensitive to third‐generation lorlatinib. When in compound with one or more ALK KDMs, resistance to lorlatinib is expected. In the case of rampantly progressive disease, rebiopsy and redefining biology in a timely manner may be informative. Abstract : This report underscores the importance of genetic analysis of serial biopsies to capture the dynamic therapeutic vulnerabilities within a patient's tumor, while providing a perspective on the complexity of ALK tyrosine kinase inhibitor treatment sequencing. Two cases are presented to illustrate the experiences of patients with advanced ALK ‐rearranged non‐small cell lung cancer, including the effect on their quality of life and the need for holistic care.